2016
DOI: 10.1002/jbm.a.35831
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticle-induced dysfunction of cardiac hemodynamics is involved in cardiac inflammation in mice

Abstract: In the past two decades, titanium dioxide nanoparticles (TiO NPs) have been extensively used in medicine, food industry and other daily life, while their possible interactions with the their influence and human body on human health remain not well understood. Thus, the study was designed to examine whether long-term exposure to TiO NPs cause myocardial dysfunction which is involved in cardiac lesions and alter expression of genes and proteins involving inflammatory response in the mouse heart. The findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…In the current study, there were deeply eosinophilic necrotic muscle fibers with pyknotic nuclei and hemorrhage was present between the cardiomyocytes in the treated group. Similar results were reported by Sheng et al (2013) and Hong et al (2016). In this study, inflammatory infiltration was observed in the myocardium and epicardium of TiO 2 NPs treated group by light microscopic examination and the monocyte cell was detected in the interstitium by electron microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, there were deeply eosinophilic necrotic muscle fibers with pyknotic nuclei and hemorrhage was present between the cardiomyocytes in the treated group. Similar results were reported by Sheng et al (2013) and Hong et al (2016). In this study, inflammatory infiltration was observed in the myocardium and epicardium of TiO 2 NPs treated group by light microscopic examination and the monocyte cell was detected in the interstitium by electron microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Titanium alloys may also be a source of TiO2 [69]. Exposure to TiO2 nanoparticles was linked to cardiac inflammation [22,70], brain damage [71], impairment of spatial recognition memory [72] and learning abilities [73] in mice. Concerns have also been raised over possible genotoxicity and carcinogenicity of titanium debris [74].…”
Section: Adverse Effects Of Titanium Debrismentioning
confidence: 99%
“…Daily gastrointestinal administration of TiO 2 NPs at 0, 2, 10, 50 mg/kg in rats for up to three months resulted in cardiac dysfunction and inflammatory response [ 7 ]. Intragastric feeding of mice with TiO 2 NPs for nine consecutive months resulted in their accumulation in the heart causing inflammation, apoptosis and cardiac dysfunction [ 8 ].…”
Section: Introductionmentioning
confidence: 99%